Ventricular septal rupture following acute myocardial infarction - a rare complication - Hossain, Muhammad Mobarock; Zaman, SM Mostafa; Khaled, Fakhrul Islam; Kabir, Mohammad Faisal Ibn; Mohammad, Noor; Rahman, Mohammad Abdur; Joarder, Ariful Islam; Islam, Anita Marium; Hoque, Harisul (University Heart Journal, 2015)
Abstract not available University Heart Journal Vol. 9, No. 2, July 2013; 121-123